Development of nano-satellite : an automated instrumentation for testing of a nano-satellite - Dhika Satria Pratyangga (2011)
A first Singapore‟s Nano-Satellite, VELOX-I is currently being built by Nanyang Technological University. This multi-mission Nano-Satellite has to be ensured working well before launching the Nano-Satellite to the space. Hence, VELOX-I has to undergo integrated system testing and every subsystem inside VELOX-I has to be tested carefully. In this project, automated instrumentations for evaluating performance of VELOX-I integrated system and for testing of two subsystems; Power Supply System (PSS) and sun sensor have been developed to examine VELOX-I performance.